The Limits of Police Investigators Discretion in Determining Suspects A Due Process of Law Perspective in the New Criminal Code - Muhammad Nizam Taftazani; Maman Budiman (PALAR | PAKUAN LAW REVIEW, 2026)
The determination of suspects as part of a forced effort in Law Number 20 of 2025 demands stricter restrictions on the scope of investigators' assessments, especially after the expansion of the type of evidence and the absence of judicial control before the determination is made. This study aims to analyze the limits of police investigators' discretion in determining suspects, the implications of expanding evidence, and the adequacy of pretrial as a protection mechanism based on the principle of due process of law. The research uses normative legal methods that are descriptive-analytical and prescriptive, with legislative and conceptual approaches. Legal materials are collected through literature studies and document studies, then analyzed qualitatively. The results of the study show that the requirement of a minimum of two pieces of evidence is not enough to be assessed based on the number, but must include the validity of the acquisition, authenticity, reliability, relevance, suitability between evidence, and the relationship of evidence with the crime and the person determined. The discretion of the investigator is not a free authority, but is limited by legality, purpose of investigation, procedure, presumption of innocence, proportionality, reasonable, and effective supervision. Pretrial remains important as judicial control after the determination of the suspect, but the examination needs to include the validity and relevance of the evidence without entering into a misdemeanor. Keywords: Investigator Discretion, Suspect Determination, Due Process of Law, Pretrial.